Climate Risk Management in Agricultural Extension - Kenya Reference Guide (Nationally Endorsed Edition) - Hansen, James; Dinku, Tufa; Trzaska, Sylwia; Grossi, Amanda; Huyer, Sophia; Moore, Maya; Ruirie, Onesmus; Ngari, Peterson; Okach, Lucas; Murage, Paul; Kiambe, Kevin; Ngesa, Janet; et al. (2025)
The Climate Risk Management in Agricultural Extension (CRMAE) Kenya Reference Guide equips agricultural extension officers with practical tools to integrate climate information into decision-making and advisory services. Developed under the Ministry of Agriculture and Livestock Development, it aligns with Kenya’s National Climate Change Action Plan, the National Framework for Climate Services, and global initiatives such as the Global Framework for Climate Services and AU Climate Change Strategy. By translating science into actionable guidance, the guide supports extension providers in delivering climate-smart solutions that enhance resilience, improve coordination, and strengthen the capacity of farmers, pastoralists, and fisherfolk across Kenya.